Answer

Verified

395.1k+ views

**Hint:**For answering this question we will use the given expression in each part and arrange all the terms containing $x$ to the left hand side from the right hand side and then simplify it as required per situation and get the value of $x$ .

**Complete step by step answer:**

Now considering from the question we have the given expression in the first part is $2\left( 5x-3 \right)-3\left( 2x-1 \right)=9$ .

By simplifying the left hand side we will have $10x-6-6x+3=9$ .

By further simplifying we will have $4x-3=9$.

After transferring the like terms aside, that is the non $x$ terms on the right hand side we will have $4x=9+3$ .

So we will have $4x=12$ .

Hence we will have $x=3$ for the first part.

Now considering from the question we have the given expression in the second part is $\dfrac{x}{2}=\dfrac{x}{3}+1$ .

After transferring the like terms aside, that is the $x$ terms on the left hand side we will have $\dfrac{x}{2}-\dfrac{x}{3}=1$ .

By further simplifying the left hand side we will have $\dfrac{3x-2x}{6}=1$ .

By simplifying this we will have $x=6$.

Hence we will have $x=6$ for the second part.

Now considering from the question we have the given expression in the third part is $\dfrac{x}{2}+\dfrac{x}{3}=\dfrac{2x}{5}-1$ .

After transferring the like terms aside that is the $x$ terms on left hand side we will have $\dfrac{x}{2}+\dfrac{x}{3}-\dfrac{2x}{5}=1$ .

By further simplifying the left hand side we will have $\dfrac{3x+2x}{6}-\dfrac{2x}{5}=1$ .

By simplifying this we will have

$\begin{align}

& \dfrac{5x}{6}-\dfrac{2x}{5}=1 \\

& \Rightarrow \dfrac{25x-12x}{30}=1 \\

\end{align}$ .

So we will have $\dfrac{13x}{30}=1$ .

Hence we will have $x=\dfrac{30}{13}$ for the third part.

**Note:**While answering questions of this type we should take care while performing the calculations for example in the third part if we had made a mistake and written as $\dfrac{25x-12x}{30}=1\Rightarrow \dfrac{12x}{30}=1\Rightarrow x=\dfrac{5}{2}$ which is clearly wrong. The important point that we use here is that the left hand side and the right hand side of an expression are always equal to each other. We can substitute the value of x and then check if the right hand side and left hand side are the same or not.

Recently Updated Pages

Differentiate between Shortterm and Longterm adapt class 1 biology CBSE

How do you find slope point slope slope intercept standard class 12 maths CBSE

How do you find B1 We know that B2B+2I3 class 12 maths CBSE

How do you integrate int dfracxsqrt x2 + 9 dx class 12 maths CBSE

How do you integrate int left dfracx2 1x + 1 right class 12 maths CBSE

How do you find the critical points of yx2sin x on class 12 maths CBSE

Trending doubts

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

List some examples of Rabi and Kharif crops class 8 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE